Numerical Modeling of Vacuum Heat Treatment of Nickel-based Superalloys - Cosentino, F; Warnken, N; Gebelin, J; Reed, R (2013)
Numerical modeling is carried out of the heat transfer effects arising during heat treatment of single-crystal nickel-based superalloys, of the type used for high pressure turbine blades in jet engines. For these components, fine control of the thermal history during processing is needed to avoid incipient melting and to develop the properties needed for service applications. Computational fluid dynamics methods are employed for the analysis. The modeling is used to predict the temporal evolution of the temperature distribution inside the treated component, to calculate heat transfer coefficients, and to analyze the homogeneity of heat transfer. The impact of the boundary conditions is investigated with particular emphasis on the temperature of the heating elements. Its value was derived from an analytical model of the furnace using effective view factors. The predictions of the modeling are tested against measurements made on laboratory-scale apparatus containing features of production-scale equipment. © 2013 The Minerals, Metals and Materials Society and ASM International.